Black phosphorus nonvolatile transistor memory. Issue 17 (14th April 2016) - Lee, Dain; Choi, Yongsuk; Hwang, Euyheon; Kang, Moon Sung; Lee, Seungwoo; Cho, Jeong Ho
Abstract : We demonstrated nanofloating gate transistor memory devices (NFGTMs) using mechanically-exfoliated few-layered black phosphorus (BP) channels and gold nanoparticle (AuNPs) charge trapping layers. Abstract : We demonstrated nanofloating gate transistor memory devices (NFGTMs) using mechanically-exfoliated few-layered black phosphorus (BP) channels and gold nanoparticle (AuNPs) charge trapping layers. The resulting BP-NFGTMs exhibited excellent memory performances, including the five-level data storage, large memory window (58.2 V), stable retention (10 4 s), and cyclic endurance (1000 cycles).